Skin prick test reactivity to common airborne pollens and molds in allergic rhinitis patients - Wan Leman, Wan Ishlah; Gendeh, Balwant Singh (Malaysian Medical Associations, 2005)
Allergic rhinitis is the single most common chronic allergic disease affecting an estimated four million people in Malaysia. House dust mites, grass pollens and fungal spores play has been identified to play a major role in the pathogenesis of allergic rhinitis. However, sensitization to pollen and spores in Malaysia is not well documented. On the basis of the results of an aerobiological survey of the common mold spores and pollens in the Klang Valley, twelve local extracts of molds and two local extracts of grass pollens were prepared by the Institute for Medical Research for this study. The study evaluated the prevalence of skin prick test (SPT) reactivity to the extracts of those airborne molds and pollens in allergic rhinitis patients in the Klang Valley. A total of 85 allergic rhinitis patients were recruited. All molds and grass pollens extracts tested, elicited positive response to SPT. Among the molds extracts, Fusarium was observed to have the highest prevalence of SPT reactivity (23.5%), followed by Aspergillus flavum (21.2%), Dreselera orysae (18.8%), Alternaria sp (17.6%), Curvularis eragrostidis (17.6%), Penicillium oxa (16.5%), Pestolotriopsis gtuepini (16.5%), Rhizopphus arrhi (16.5%), Aspergilluls nigus (15.3%). Penicillium choy (12.9%), Aspergillus fumigatus (11.8%), and Cladosporium sp (4.7%). In the grass pollen, the SPT reactivity to Ischaemum and Enilia is 14.1% and 5.9% respectively. However, the prevalence of SPT reactivity was not influenced by the age, sex, ethnicity, symptomatology and concurrent allergic condition. We have documented the prevalence of skin prick test reactivity to common molds and grass pollens in the Klang valley, which is comparable to the neighboring countries. Its prevalence in our allergic rhinitis patients suggests that it has a role in pathogenesis of allergic diseases. A larger representative sample involving multi-centric centers in Malaysia should be encouraged in the near future.